Sistem Informasi Digital dan Pencari Jalan - Lisna Sukmawati; Jaswandi .; Adidin Aidin Maulana; Abdul Rahman (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2019)
Generally new students and new visitors in a building often experience difficulties when searching for a space, especially a building that has a lot of space. As well as having a complex space, both classrooms and staff workspaces. Usually visitors who have just entered the building's environment ask the security information parties or other visitors to provide information on classrooms or staff workspace sought. Another way for visitors to find information on conventional building space is available, but the alternative method requires a lot of time. For this reason, this study was made in the campus building, using NetBeans IDE software applying the closest path search algorithm based on the pixel index value on the map image. The system will display the closest landing map and information on the lecturer room staff room and lecture classrooms and search for lecturer data information. Likewise the search for staff and lecturers by writing their names in the search panel on the touch screen monitor. then pressing the "take me there" button, the system will show the direction to the workspace and provide staff information. To view announcement information, users simply select the announcement menu, then choose the announcement category. With this system, visitors are expected to have no difficulties in finding space and staff and campus information. The purpose of this study is to be able to provide a map of the direction of the building on campus from the position of the system to the classroom and the staff room and lecturer room. Besides that, it can also provide information about campus activities, announcements and even events to students and visitors, designed with an attractive interface that is easy to use. Keywords: Building Map, Waifinding, Digital Information, LCD screen, NetBeans IDE